The Effect of the Parameters of Robotic TIG Welding on the Microstructure of 17-4PH Stainless Steel Welded Joint - A. Nalborczyk-Kazanecka; G. Mrowka-Nowotnik (Archives of Metallurgy and Materials, 2023)
17-4PH stainless steel finds application in the aerospace industry owing to its good mechanical properties and corrosion resistance. In the literature, this steel is described as good for welding, but research shows that it may be problematic due to the formation of defects. In this study, the welded joints were made by the robotic TIG welding method with various welding speeds (2 and 3 mm/s). The joints were subjected to non-destructive testing and were free from defects. The microstructure was observed by light microscopy and scanning electron microscopy. Changes in the microstructure of the heat affected zone were observed and discussed. Based on the observation of the microstructure and the change in the hardness profile, the heat affected zone was divided into 4 characteristic regions. δ-ferrite and NbC were observed in the martensite matrix. The welded joints were subjected to heat treatment consisting of solution and aging in 550°C for 4 h. The microstructure of the heat affected zone become homogenized as a result of the heat treatment. The content of stable austenite in the welded joint after the heat treatment was about 3%.